A simplified reverse wire technique using an angulated supercross microcatheter. Issue 1 (23rd August 2019) - Chan, Yu Ho; Cheng, Victor Yue Hong; Wong, Chi Wing; Lam, Cheuk Sum
Abstract: Bifurcation lesion with an extreme angulated side branch remains a challenge in coronary intervention. Reverse wire technique was originally described by Dr. Kawasaki and nowadays this can be done by double‐lumen catheter. We report a novel "simplified reverse wire technique with a specialized angle tip microcatheter, " Supercross microcatheter™ (Teleflex). This can facilitate wiring of extreme angulated side branch by this simple and feasible method without using double lumen catheter.